Age and dose dependent changes to the bone and bone marrow microenvironment after cytotoxic conditioning with busulfan - Abbasizadeh, Nastaran; Burns, Christian S.; Verrinder, Ruth; Ghazali, Farhad; Seyedhassantehrani, Negar; Spencer, Joel A. (Frontiers in Cell and Developmental Biology, 2024)
Preparative regimens before Hematopoietic Cell Transplantation (HCT) damage the bone marrow (BM) microenvironment, potentially leading to secondary morbidity and even mortality. The precise effects of cytotoxic preconditioning on bone and BM remodeling, regeneration, and subsequent hematopoietic recovery over time remain unclear. Moreover, the influence of recipient age and cytotoxic dose have not been fully described. In this study, we longitudinally investigated bone and BM remodeling after busulfan treatment with low intensity (LI) and high intensity (HI) regimens as a function of animal age. As expected, higher donor chimerism was observed in young mice in both LI and HI regimens compared to adult mice. Noticeably in adult mice, significant engraftment was only observed in the HI group. The integrity of the blood-bone marrow barrier in calvarial BM blood vessels was lost after busulfan treatment in the young mice and remained altered even 6 weeks after HCT. In adult mice, the severity of vascular leakage appeared to be dose-dependent, being more pronounced in HI compared to LI recipients. Interestingly, no noticeable change in blood flow velocity was observed following busulfan treatment. Ex vivo imaging of the long bones revealed a reduction in the frequency and an increase in the diameter and density of the blood vessels shortly after treatment, a phenomenon that largely recovered in young mice but persisted in older mice after 6 weeks. Furthermore, analysis of bone remodeling indicated a significant alteration in bone turnover at 6 weeks compared to earlier timepoints in both young and adult mice. Overall, our results reveal new aspects of bone and BM remodeling, as well as hematopoietic recovery, which is dependent on the cytotoxic dose and recipient age.